The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.31223/osf.io/7x3sh
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The seismic history of the Pisia fault (eastern Corinth rift, Greece) from fault plane weathering features and cosmogenic 36Cl dating

Abstract: The deformation of the eastern Corinth rift (Greece) is distributed along several E-W trending active normal faults. Here, the 25-km-long Pisia fault experienced up to 150 cm of coseismic displacement during the 1981 Alkyonides earthquake sequence (M = 6.7, 6.4, 6.3). Using terrestrial laser scanning, coupled with analyses of color changes, lichen colonization and karstic features, we identify differentially weathered horizontal stripes on the exposed Pisia fault plane. The stripe boundaries occur at scarp hei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(34 citation statements)
references
References 53 publications
3
31
0
Order By: Relevance
“…Specifically, analysis of post-LGM slip on the Pisia fault revealed maximum slip rates of 2.3 mm/yr during the Holocene (Mechernich et al, 2018). Palaeoseismic trenching along the Skinos fault yielded throw rates of 1.2-2.5 mm/yr over ~1500 years (Collier et al, 1998).…”
Section: Tectonic Settingmentioning
confidence: 99%
“…Specifically, analysis of post-LGM slip on the Pisia fault revealed maximum slip rates of 2.3 mm/yr during the Holocene (Mechernich et al, 2018). Palaeoseismic trenching along the Skinos fault yielded throw rates of 1.2-2.5 mm/yr over ~1500 years (Collier et al, 1998).…”
Section: Tectonic Settingmentioning
confidence: 99%
“…The age of active fault scarps in Greece and western Turkey is primarily constrained by cosmogenic dating which suggests that climatic conditions were favorable for scarp formation from 16.5 ± 2 ka to the present day (Benedetti et al., 2003, 2013; Mechernich et al., 2018; Mouslopoulou et al., 2014; Mozafari et al., 2019). Historical earthquakes in the Mediterranean region support the interpretation that the majority of slip recorded by limestone fault scarps accrues during earthquakes (Benedetti et al., 2003, 2013; Mechernich et al., 2018; Mozafari et al., 2019). The earthquake‐slip model for scarp formation in Crete is also consistent with observations from cultural strain markers (e.g., roads and fences) constructed last century that show no evidence of creep on active faults at the ground surface (this study).…”
Section: Tectonic Setting and Active Faultsmentioning
confidence: 99%
“…(e.g., McCalpin, 2009), geological records significantly contribute to examining whether there is a certain regularity of recurrence intervals and magnitudes of large earthquakes (e.g., Shimazaki and Nakata, 1980;Schwartz and Coppersmith, 1984;Grant, 1996;Weldon et al, 2004;Zielke et al, 2015). Although many studies have presented evidence that faults appear to behave regularly with regard to the size and recurrence intervals of large earthquakes (e.g., Klinger et al, 2011;Berryman et al, 2012), others have reported fluctuations (e.g., Chen et al, 2007;Schlagenhauf et al, 2011;Rockwell et al, 2015;Komori et al, 2017;Scharer et al, 2017;Mechernich et al, 2018;Wechsler et al, 2018). This raises the question of how variable earthquake recurrences are in terms of their size and recurrence interval.…”
Section: Introductionmentioning
confidence: 99%